2015
DOI: 10.1111/dom.12534
|View full text |Cite
|
Sign up to set email alerts
|

Once‐weekly glucagon‐like peptide‐1 receptor agonist dulaglutide is non‐inferior to once‐daily liraglutide and superior to placebo in Japanese patients with type 2 diabetes: a 26‐week randomized phase III study

Abstract: AimsTo examine the efficacy and safety of once‐weekly dulaglutide monotherapy (0.75 mg) compared with placebo and once‐daily liraglutide (0.9 mg) in Japanese patients with type 2 diabetes.MethodsThis was a phase III, 52‐week (26‐week primary endpoint), randomized, double‐blind, placebo‐controlled, open‐label comparator (liraglutide) trial comparing 492 Japanese patients with type 2 diabetes (dulaglutide, n = 281; liraglutide, n = 141; and placebo, n = 70) who were aged ≥20 years. Patients and investigators wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
178
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(199 citation statements)
references
References 36 publications
20
178
1
Order By: Relevance
“…To evaluate changes in HbA1c and body weight by sex, subgroup analyses were conducted using the mixed model for repeated measures used for the primary efficacy analyses in the studies [8,9], with a term for sex and terms for treatment-by-sex, visit-by-sex, and treatment-by-sex-by-visit interactions added. Least-squares mean changes for HbA1c and body weight by treatment and sex were estimated.…”
Section: Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate changes in HbA1c and body weight by sex, subgroup analyses were conducted using the mixed model for repeated measures used for the primary efficacy analyses in the studies [8,9], with a term for sex and terms for treatment-by-sex, visit-by-sex, and treatment-by-sex-by-visit interactions added. Least-squares mean changes for HbA1c and body weight by treatment and sex were estimated.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Least-squares mean changes for HbA1c and body weight by treatment and sex were estimated. To further explore the relationship between changes in HbA1c and body weight, changes from baseline in HbA1c and body weight at endpoint for individual patients were presented on scatter plots, and Pearson correlations between the changes weeks of treatment in 2 randomized, controlled phase 3 studies in Japanese patients with T2D, dulaglutide 0.75 mg was shown to be noninferior to liraglutide 0.9 mg [8] for changes in HbA1c and superior to insulin glargine [9] for changes in HbA1c, with a lower incidence of hypoglycemia. In the third phase 3 study (nonrandomized, noncontrolled) in Japanese patients, dulaglutide 0.75 was overall safe and effective over 52 weeks of treatment when used in combination with a single oral hypoglycemic agent from among 5 classes (sulfonylureas, biguanides, α-glucosidase inhibitors, thiazolidinedione, or glinides) [10].…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…gov (NCT01584232, NCT01558271, NCT01468181). Study design and methods for each study have been previously reported [7][8][9][10].…”
Section: Patientsmentioning
confidence: 99%
“…In phase 3 studies in Japanese patients with T2D, once weekly dulaglutide 0.75 mg has shown superiority to insulin glargine (in a randomized, 26-week, open-label study of dulaglutide in combination with sulfonylureas [SU] and/or biguanides [BG]) and non-inferiority to liraglutide 0.9 mg/day (in a randomized monotherapy study in which dulaglutide was compared to placebo [double-blind] and to liraglutide 0.9 mg/day [open-label]; the study had a 26-week primary endpoint and a 52-week treatment period) in HbA1c changes [7][8][9]. Also, in a nonrandomized, open-label, long-term (52-week) phase 3 safety study in Japanese patients with T2D, once weekly dulaglutide 0.75 mg was overall well-tolerated in combination with a single oral hypoglycemic agent (SU, BG, α-glucosidase inhibitors, thiazolidinediones, or glinides) [10].…”
mentioning
confidence: 99%